Nickel-titanium alloy orthodontic arch wire and preparation method thereof
By using nickel-titanium alloy materials and multi-step process treatment, orthodontic arch wires with super elasticity and shape memory characteristics were prepared, which solved the problems of insufficient correction force and poor corrosion during the movement of the teeth, and achieved higher wear comfort, correction effect and product life.
Patent Information
- Application Number
- CN202411961340.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-05-09
AI Technical Summary
Traditional stainless steel orthodontic archwires are difficult to provide continuous and gentle orthodontic force during tooth movement, and are prone to corrosion in the oral environment, releasing metal ions is potentially cytotoxic to the periodontal membrane and gingival cells, affecting the treatment effect and patient comfort.
Orthodontic arch wire made of nickel-titanium alloy material improves the superelastic and shape memory characteristics of the arch wire through processes such as heat extraction, diameter reduction, resistance furnace annealing, pickling and constant temperature setting, reducing surface cracks and oxide films, and enhancing corrosion resistance and resistance.
Nitinol orthodontic archwires can self-recover after tooth movement, reduce periodontal tissue damage, provide continuous soft orthodontic power, improve wear comfort and orthodontic effect, extend product life, and reduce potential toxicity to the periodontal membrane and gums.
Smart Images

Figure CN119956160A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of medical devices, and in particular to a nickel-titanium alloy orthodontic arch wire and a preparation method thereof. Background Art
[0002] Orthodontic archwire is one of the key devices in orthodontic treatment. It is mainly used to transmit correction force and guide teeth to move to the ideal position. It is an important part of fixed orthodontic appliances. It is connected to teeth through brackets and uses the rebound force generated by its elastic deformation to achieve tooth displacement and arch shape adjustment. The development of orthodontic archwire is closely related to the progress of material science. Its performance directly affects the correction effect, treatment cycle and patient comfort.
[0003] However, due to the high elastic modulus of the traditional stainless steel archwire, it is difficult to provide continuous and gentle correction force during tooth movement, resulting in limited tooth displacement and prolonged treatment cycle. At the same time, these archwires are prone to corrosion in the complex environment of the oral cavity, releasing metal ions such as nickel and chromium. Studies have shown that these ions are potentially cytotoxic to periodontal ligament cells and gingival fibroblasts. Long-term exposure may induce local inflammatory reactions and even cause contact allergic reactions in some patients. In addition, the microbial community and its metabolites in the oral cavity will accelerate the degradation of the archwire surface, change its mechanical properties, and further affect the correction effect.
[0004] Therefore, how to improve the wearing comfort of orthodontic arch wire is an urgent problem that needs to be solved. Summary of the invention
[0005] In view of the above problems, a nickel-titanium alloy orthodontic arch wire and a preparation method thereof are proposed to overcome the above problems or at least partially solve the above problems, comprising the following steps: Step 1: hot-draw the archwire twice, and pass the archwire through a reducing mold to reduce its diameter. The hot-drawing temperature is 600°C to 700°C, and the wire drawing wheel speed is 1.5r / min to 2.5r / min. Step 2: Heat the arch wire in a 750℃ resistance furnace and then cool it to room temperature. After cooling, cold draw the arch wire twice; Step 3: Straighten the cold-drawn archwire, pickle it for 3-5 minutes, and then shape it at a constant temperature of 525℃; Step 4: The shaped arch wire is acid-washed for the second time; Step 5: Fine polish the arch wire after secondary pickling to obtain the finished arch wire.
[0006] Optionally, the diameter of the raw material of the arch wire is 1 mm, and the diameter of the arch wire after diameter reduction is uniformly 0.6 mm.
[0007] Optionally, the variable diameter mold includes at least one of the following: a mechanical variable diameter mold, a pneumatic variable diameter mold, a hydraulic variable diameter mold, and a composite material variable diameter mold.
[0008] Optionally, the straightening temperature for straightening the cold-drawn arch wire is 400°C.
[0009] Optionally, the solution ratio during pickling is HF:HNO3:H2O=1:10:240.
[0010] Optionally, the nickel content in the finished arch wire is 50 at% to 60 at%, and the titanium content is 40 at% to 50 at%.
[0011] Optionally, the technique used for fine polishing is electrochemical polishing.
[0012] Optionally, before hot-pulling the arch wire, the method further includes: uniformly spraying a high-temperature lubricant on the surface of the arch wire.
[0013] Optionally, it is characterized in that the high-temperature lubricant includes at least one of the following: graphite-based lubricant, saponified liquid, and glass lubricant.
[0014] A nickel-titanium alloy orthodontic arch wire is prepared by the above preparation method.
[0015] The orthodontic arch wire provided by the present invention is subjected to resistance furnace annealing treatment, which reduces the presence of surface cracks, forms an oxide film to allow the grains to recrystallize and improve the surface smoothness, and multiple drawing is conducive to the consistency of the texture direction of the arch wire surface, so that the initial cracks and burrs are smaller; constant temperature shaping improves the surface smoothness, reduces notches and depressions, ensures the opening of the arch wire, improves the comfort of human oral wearing, and has certain corrosion resistance and resistance, and can ensure that it is not easy to deform and damage in the constant temperature environment of the oral cavity, thereby improving the product life. In addition, the finished nickel-titanium alloy arch wire has superelasticity, which can meet the ability of self-recovery after tooth activity and reduce the damage to periodontal tissue. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings required for use in the description of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0017] Figure 1 This is a flowchart of a method for preparing a nickel-titanium alloy orthodontic archwire provided by one embodiment of the present invention; Figure 2 This is a SEM schematic diagram of hot drawing in a method for preparing a nickel-titanium alloy orthodontic arch wire provided by one embodiment of the present invention; Figure 3 It is a SEM schematic diagram of annealing and pickling in a method for preparing a nickel-titanium alloy orthodontic arch wire provided by one embodiment of the present invention; Figure 4 This is a SEM schematic diagram of cold drawing in a method for preparing a nickel-titanium alloy orthodontic arch wire provided in one embodiment of the present invention; Figure 5 This is a SEM schematic diagram of straightening and pickling in a method for preparing a nickel-titanium alloy orthodontic arch wire provided in one embodiment of the present invention; Figure 6 It is an electron microscope spectrum and a schematic diagram of nickel-titanium content distribution of a finished arch wire in a method for preparing a nickel-titanium alloy orthodontic arch wire provided by one embodiment of the present invention; Figure 7 It is an XRD diffraction pattern of a partial processing process in a method for preparing a nickel-titanium alloy orthodontic arch wire provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0018] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The existing arch wires have poor elasticity and displacement restrictions when teeth move during orthodontics due to their own material properties and installation stereotypes, which affects the correction effect. The released ions have potential cytotoxicity to the periodontal membrane and gingival fibroblasts. Long-term use may cause allergic reactions. The arch wire morphology and mechanical structure change due to the influence of the flora in the oral environment. Orthodontic arch wires made of nickel-titanium alloy have superelasticity and shape memory functions. They can return to their original shape at oral temperature, and apply continuous and gentle force to promote tooth movement during the entire treatment process. They have a gentle correction force to improve the user's comfort, thereby reducing the number of follow-up visits, shortening the course of treatment and improving the efficacy. Secondly, the excellent corrosion resistance of nickel-titanium arch wires makes them more durable in the oral environment.
[0020] Reference Figure 1 , shows a flowchart of a method for preparing a nickel-titanium alloy orthodontic archwire according to an embodiment of the present invention, which may specifically include the following steps: Step 1: hot-draw the archwire raw material twice, and pass the archwire after the two hot-drawings through a reducing mold to reduce its diameter, thereby completing the initial plastic deformation of the archwire, wherein the hot-drawing temperature is 600℃~700℃, and the wire drawing wheel speed is 1.5r / min~2.5r / min.
[0021] Hot drawing is to heat the material and pull it in the mold to make the material plastically deform, thereby changing its shape and size, such as Figure 2 shown.
[0022] In an embodiment of the present invention, before the arch wire is hot-pulled, the method further includes: uniformly spraying a high-temperature lubricant on the surface of the arch wire.
[0023] It is understandable that during the hot drawing process, there will be a large friction between the arch wire and the die, and the friction will generate additional heat, which may cause local overheating of the arch wire and affect its mechanical properties. Lubricants can reduce frictional heat, ensure that the arch wire maintains a uniform temperature during the drawing process, and prevent scratches on the arch wire surface or wear on the die.
[0024] Since hot drawing is performed at high temperature (600℃~700℃), the lubricant needs to have high heat resistance and be able to maintain stable lubrication performance at high temperature. In the embodiment of the present invention, at least one of the following lubricants can be used for lubrication: graphite-based lubricant, saponified liquid, glass lubricant.
[0025] Specifically, before spraying the lubricant, the surface of the arch wire needs to be cleaned to remove oil, dust and other impurities to ensure that the lubricant can adhere evenly. Use a spraying device to evenly spray the high-temperature lubricant on the surface of the arch wire. When spraying, it is necessary to control the amount and uniformity of the spray to ensure that the lubricant covers the entire surface of the arch wire. After spraying, the lubricant may need to be dried or cured at a certain temperature to form a stable lubricating film. The specific drying or curing conditions depend on the type of lubricant.
[0026] In the embodiment of the present invention, after the lubrication treatment is completed, the arch wire raw material needs to be hot-drawn twice. It is understandable that one hot-drawing may not fully achieve the desired deformation effect, so a second hot-drawing is required to ensure that the material can be uniformly deformed. Moreover, the phase change behavior of the nickel-titanium alloy can be controlled by applying stress through heat treatment and drawing and reducing the diameter, thereby adjusting its mechanical properties to achieve better orthodontic effects. In addition, multiple drawing is also conducive to the consistency of the texture direction of the arch wire surface, so that the cracks and burrs generated in the early stage are smaller.
[0027] In the embodiment of the present invention, a variable diameter mold can be used to achieve the diameter change of the arch wire. Specifically, the variable diameter mold can include at least one of the following: a mechanical variable diameter mold, a pneumatic variable diameter mold, a hydraulic variable diameter mold, and a composite material variable diameter mold. Those skilled in the art can freely choose according to actual needs, and the embodiment of the present invention does not limit this.
[0028] In the embodiment of the present invention, the diameter of the arch wire raw material can be 1mm, and the diameter of the arch wire after the diameter reduction mold is reduced can be uniformly 0.6mm. It can be understood that the arch wire is reduced to 0.6mm during the drawing process, and the light structure is conducive to the subsequent card holder installation and improves the comfort of oral wearing. Of course, the embodiment of the present invention can also adjust the diameter of the arch wire after the diameter reduction according to the specific conditions of the oral cavity of different patients.
[0029] Step 2: Heat the arch wire in a 750℃ resistance furnace and then cool it to room temperature. After cooling, cold draw the arch wire twice to complete the secondary plastic deformation of the arch wire.
[0030] In the embodiment of the present invention, by heating the arch wire to 750°C, the grain structure inside the arch wire can be recrystallized, eliminating the internal stress generated in the material during the previous processing, thereby making the grain structure more uniform, reducing internal defects, and improving the plasticity and toughness of the material, which is convenient for subsequent cold drawing processing, such as Figure 3 shown.
[0031] Furthermore, after the archwire is heated in the resistance furnace, it needs to be cooled to room temperature. It is understandable that slow cooling can make the phase change process inside the material more stable and avoid stress concentration or deformation caused by rapid cooling.
[0032] In an embodiment of the present invention, after the archwire is cooled to room temperature, it can be cold-drawn twice to improve the strength and hardness of the material. It is understandable that during the cold-drawing process, the grain structure of the material will be arranged along the drawing direction, thereby improving its mechanical properties and ensuring that it can apply a continuous and gentle correction force during the orthodontic process. Through two cold-drawings, plastic deformation can be gradually achieved to avoid excessive deformation at one time, which may cause material damage. Figure 4 During the cold drawing process, a lubricant can also be sprayed on the surface of the archwire.
[0033] In the embodiment of the present invention, the arch wire is annealed in a resistance furnace to reduce the presence of surface cracks and form an oxide film to allow the grains to recrystallize and improve the surface smoothness.
[0034] Step 3: Straighten the cold-drawn archwire, pickle it for 3 to 5 minutes, and then shape it at a constant temperature of 525℃.
[0035] It should be understood that during the cold drawing process, the arch wire may bend or twist due to uneven stress distribution, and straightening can restore it to a straight state. After straightening, the straightness and dimensional accuracy of the arch wire are improved, which can ensure that it meets the requirements of orthodontic applications to a certain extent.
[0036] In an embodiment of the present invention, the straightening temperature for straightening the cold-drawn arch wire is 400°C.
[0037] It is understandable that 400°C is a critical temperature range for nickel-titanium alloys. At this temperature, the material is in a transition state between the austenite phase and the martensite phase, which makes it easy to adjust its mechanical properties through straightening. Moreover, the temperature is high enough to allow the material to undergo a certain recrystallization and eliminate the internal stress generated during the cold drawing process, but it will not cause excessive softening of the material. Straightening at 400°C allows the arch wire to be more easily plastically deformed while maintaining a certain strength, thereby achieving the purpose of straightening. By heating and straightening, the superelasticity and shape memory properties of the material can be further optimized, allowing it to play a better role in the orthodontic process. This process step is an important link in ensuring that the final nickel-titanium alloy orthodontic arch wire has excellent performance and reliability.
[0038] In an embodiment of the present invention, after the arch wire is straightened, it needs to be pickled for 3 to 5 minutes, wherein the solution ratio during pickling is HF:HNO3:H2O=1:10:240.
[0039] It is understandable that during the straightening process, an oxide layer may form on the surface of the arch wire. Pickling can effectively remove this oxide layer and make the surface cleaner. At the same time, pickling can remove tiny particles, oil stains or other impurities on the surface of the arch wire, improve the surface finish, and help form a protective oxide film in subsequent processes to improve its corrosion resistance in the oral environment. In addition, pickling can also remove harmful substances on the surface (such as nickel ions), reduce potential toxicity to oral tissues, and improve the biocompatibility of the arch wire.
[0040] It should be noted that too short a pickling time may result in incomplete cleaning, while too long a time may damage the surface of the material. 3 to 5 minutes of pickling time is sufficient to remove the surface oxide layer and impurities while avoiding excessive corrosion of the material. Figure 5 shown.
[0041] After the first acid wash, the arch wire needs to be shaped at a constant temperature of 525°C. Constant temperature shaping can improve the smoothness of the arch wire surface, reduce notches and depressions, ensure the opening degree of the arch wire, and improve the comfort of wearing it in the human mouth.
[0042] Step 4: The shaped arch wire is acid-washed for the second time.
[0043] During the constant temperature shaping process, a new oxide layer may form on the surface of the arch wire, and the second pickling can effectively remove this oxide layer, making the surface of the arch wire cleaner. The solution ratio of the second pickling is usually the same as the solution ratio of the first pickling, so as to ensure the consistency of the cleaning effect of the two times.
[0044] In the embodiment of the present invention, after the pickling is completed, the material can also be thoroughly cleaned with deionized water to remove the residual acid solution, and then dried.
[0045] Step 5: Fine polish the arch wire after secondary pickling to obtain the finished arch wire.
[0046] In an embodiment of the present invention, the technique used for fine polishing may be electrochemical polishing. Specifically, the arch wire may be used as an anode and placed in an electrolyte, and then appropriate current density and voltage may be applied to selectively dissolve the metal surface. After polishing, the arch wire may be thoroughly cleaned to remove residual electrolyte, and then dried. It should be noted that controlling the current density and voltage may adjust the polishing effect to avoid excessive dissolution or insufficient polishing.
[0047] After electrochemical polishing, a uniform oxide film can be formed on the surface of the archwire, which improves its corrosion resistance in the oral environment. It can also remove tiny defects and impurities on the surface, reduce irritation to oral tissues, significantly reduce microscopic protrusions and scratches on the surface, and make the surface of the archwire smoother and brighter. The smooth surface can reduce the friction between the archwire and the bracket, improve wearing comfort and correction effect, and improve the biocompatibility of the archwire.
[0048] In an embodiment of the present invention, a biocompatible coating (such as a titanium nitride coating) may be coated on the surface of the arch wire to further reduce the release of harmful ions and improve the biocompatibility and corrosion resistance of the arch wire.
[0049] like Figure 6 As shown, the nickel content in the finished arch wire provided by the embodiment of the present invention is 50at% to 60at%, and the titanium content is 40at% to 50at%.
[0050] The orthodontic arch wire provided by the present invention is subjected to resistance furnace annealing treatment, which reduces the presence of surface cracks, forms an oxide film to allow the grains to recrystallize and improve the surface smoothness, and multiple drawing is conducive to the consistency of the texture direction of the arch wire surface, so that the initial cracks and burrs are smaller; constant temperature shaping improves the surface smoothness, reduces notches and depressions, ensures the opening of the arch wire, improves the comfort of human oral wearing, and has certain corrosion resistance and resistance, and can ensure that it is not easy to deform and damage in the constant temperature environment of the oral cavity, thereby improving the product life. In addition, the finished nickel-titanium alloy arch wire has superelasticity, which can meet the ability of self-recovery after tooth activity and reduce the damage to periodontal tissue.
[0051] In another embodiment of the present invention, an XRD diffraction experiment may be performed to analyze the crystal structure changes of the nickel-titanium alloy orthodontic arch wire under different treatment processes. Specifically, the experiment may be performed according to the following steps: Sample preparation (1) Sample selection: Representative samples were selected from nickel-titanium alloy archwires after different processing techniques.
[0052] (2) Sample processing: Cut the sample into a size suitable for XRD testing (usually powder or flakes) and ensure that the sample surface is flat.
[0053] 2. Experimental parameter settings (1) X-ray source: usually a copper target (Cu Kα radiation, wavelength λ = 1.5418 Å) is used.
[0054] (2) Scanning range: The scanning angle range is usually 20° to 120°.
[0055] (3) Scanning speed: The scanning speed was set to 5° / min with a step size of 0.02° to ensure accurate measurement of the diffraction peaks.
[0056] 3. Data Collection (1) Diffraction pattern: The diffraction pattern of the sample is collected by an XRD instrument, and the diffraction angle (2θ) and diffraction intensity are recorded.
[0057] (2) Repeated testing: To ensure the reliability of the data, each sample is usually tested multiple times.
[0058] 4. Data Analysis (1) Diffraction peak identification: Identify the main diffraction peaks in the sample by comparing with standard cards (such as B2 austenite phase and B19' martensite phase of NiTi).
[0059] (2) Phase composition analysis: Analyze the phase composition and relative content of the sample based on the position and intensity of the diffraction peak.
[0060] (3) Lattice parameter calculation: The lattice parameters are calculated by Bragg's law to further analyze the changes in the crystal structure.
[0061] like Figure 7As shown, in the XRD diffraction spectrum, it can be seen that the positions of the main diffraction peaks appear at 2θ=42.8°, 61.9°, 78.2°, 93.3°, and 108.7°, which are roughly matched with the peak positions in the NiTi standard card, with an error of about ±0.2°, indicating that all samples have the crystal structure of the standard substance; in addition, different NiTi standard cards are matched at other positions, and analysis shows that the main diffraction peak is the B2 austenite phase structure of NiTi, and other matched NiTi is the B19' martensite phase structure; and, after a series of process flows, the intensity of the B19' martensite phase decreases, accompanied by the disappearance of the peak. After analysis, it may be the transformation of the martensite phase to austenite, and the alloy gradually becomes a structure stabilized by the austenite phase; at the same time, before some steps, there is still an oxide phase of Ti, which is compared with the standard card and analyzed as the TiO2 phase.
[0062] Through XRD diffraction experiments, the crystal structure changes of nickel-titanium alloys under different processing techniques can be monitored to ensure product quality. It is also possible to analyze phase change behavior, optimize process parameters such as heat treatment and drawing, and improve the mechanical properties and shape memory characteristics of nickel-titanium alloys.
[0063] It should be noted that, for the sake of simplicity, the method embodiments are described as a series of action combinations, but those skilled in the art should be aware that the embodiments of the present invention are not limited by the order of the actions described, because according to the embodiments of the present invention, certain steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also be aware that the embodiments described in the specification are all preferred embodiments, and the actions involved are not necessarily required by the embodiments of the present invention.
[0064] An embodiment of the present invention also provides a nickel-titanium alloy orthodontic arch wire. The finished arch wire has the following characteristics: it has shape memory and superelasticity, can apply corresponding force to teeth during orthodontics to ensure the correction effect, and can be restored to a predetermined shape due to superelasticity at oral temperature, and the utilization rate of the arch wire is improved by reducing the number of wire changes. It can be ensured to be not easily deformed and damaged in a constant temperature environment in the oral cavity, thereby increasing the product life. It also has a continuous light force effect, which can effectively exert a continuous light force effect, and is helpful for damage to the tooth body and periodontal tissues when the teeth move. It is also corrosion-resistant and toxic-resistant. Since the finished wire still contains oxygen elements, titanium oxidation can be performed on the surface layer to form a thin film to reduce the release of nickel and improve the biocompatibility of the alloy.
[0065] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0066] The above provides a detailed introduction to a nickel-titanium alloy orthodontic arch wire and a preparation method thereof. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a nickel-titanium alloy orthodontic arch wire, characterized in that: The method is carried out according to the following steps: Step 1: hot-draw the archwire twice, and pass the archwire through a reducing mold to reduce its diameter. The hot-drawing temperature is 600°C to 700°C, and the wire drawing wheel speed is 1.5r / min to 2.5r / min. Step 2: Heat the arch wire in a 750°C resistance furnace and then cool it to room temperature, and then cold draw the arch wire twice after cooling; Step 3: Straighten the cold-drawn archwire, pickle it for 3-5 minutes, and then shape it at a constant temperature of 525℃; Step 4: The shaped arch wire is acid-washed for the second time; Step 5: Fine polish the arch wire after secondary pickling to obtain the finished arch wire.
2. The method according to claim 1, characterized in that The diameter of the raw material of the arch wire is 1 mm, and the diameter of the arch wire after diameter reduction is uniformly 0.6 mm.
3. The method according to claim 2, characterized in that The variable diameter grinding tool comprises at least one of the following: a mechanical variable diameter grinding tool, a pneumatic variable diameter grinding tool, a hydraulic variable diameter grinding tool, and a composite material variable diameter grinding tool.
4. The method according to claim 3, characterized in that The straightening temperature for straightening the cold-drawn arch wire is 400°C.
5. The method according to claim 4, characterized in that The solution ratio during pickling is HF:HNO3:H2O=1:10:
240.
6. The method according to claim 5, characterized in that The nickel content of the finished arch wire is 50 at% to 60 at%, and the titanium content is 40 at% to 50 at%.
7. The method according to claim 6, characterized in that The technique used for the fine polishing is electrochemical polishing.
8. The method according to claim 1, characterized in that Before hot-pulling the arch wire, the method further includes: uniformly spraying a high-temperature lubricant on the surface of the arch wire.
9. The method according to claim 8, characterized in that The high temperature lubricant includes at least one of the following: graphite-based lubricant, saponified liquid, and glass lubricant.
10. A nickel-titanium alloy orthodontic archwire, characterized in that: The nickel-titanium alloy orthodontic arch wire is prepared by the preparation method described in any one of claims 1-7.